The creative screenwriter exercises to expand your craft - Waldeback, Zara; Batty, Craig (London Methuen Drama, 2012)
The film industry is seeking fresh screenwriting talent, but today's writers don't just need to be accomplished at their craft - they need to be highly creative. 'The Creative Screenwriter' is a workbook of inspiring writing exercises to sharpen the writer's talents.
Being creative -- Generating ideas -- Developing stories -- Understanding characters -- Shaping relationships -- Designing structure -- Reimagining structure -- Defining beginning and endings -- Weaving worlds -- Exploring genre and form -- Enhancing scene writing -- Strengthening visual storytelling -- Improving dialogue -- Managing rewrites -- Pefecting the pitch -- Building outlines and treatments -- Discovering voice -- DIY script surgery.
Keywords: Motion picture authorship